Современные тенденции легирования вольфрамовых твердых сплавов добавками карбидов (обзор) - Бондаренко, В.П.; Мартынова, Л.М.; Галков, А.В. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2006)
The review of publications on alloying WC–Co and WC–Ni tungsten hardmetals by additives of carbides is presented. The microadditives which are the most promising for further studies
and will allow one to improve performance characteristics of tungsten hardmetals designed for
manufacturing dies for high pressure apparatus for diamond synthesis have been found.